Property A of differential equations with positive and negative term - Jozef Džurina; Blanka Baculíková (Electronic Journal of Qualitative Theory of Differential Equations, 2017)
In the paper, we elaborate new technique for the investigation of the asymptotic properties for third order differential equations with positive and negative term \begin{equation*} \left(b(t)\left(a(t)x'(t)\right)'\right)'+p(t)f(x(τ(t)))-q(t)h(x(σ(t)))=0. \end{equation*} We offer new easily verifiable criteria for property A. We support our results with illustrative examples.